The influence of body pose angles at the beginning of pushing away on the ski jump length - Zanevsky, I.; Banakh, V. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: A significant (p =.05) correlation between flexion of the knee joint just before pushing away and the jump distance of elite ski sportsmen was found (Paradis et al. 2001). The aim of the research was to study the influence of a skiers body pose at the beginning of pushing away on the ski jump length.